Production Of Chitinase By A Locally Isolated Fungus - Berahim, Zulkarami (2007)
Chitin and chitinolytic enzymes are gaining importance for their biotechnological applications. Particularly, chitinases which have been widely used in agriculture to control plant pathogens. Chitinases and chitooligomers produced by enzymatic hydrolysis of chitin have also been used in human health care products. The success in employing chitinases for different applications depends on the supply of highly active preparations at reasonable cost. In this study, isolation and screening of fungus were carried out. Trichoderma sp. was selected due to the ability to produce chitinase enzyme with biggest clear zone formation on Chitinase Detection Agar (CDA) for qualitative confirmation. The slides were viewed under light microscope to determine the isolated fungi morphology. Shake flask fermentation using Trichoderma sp. was carried out to produce chitinase enzyme. Different types of media were investigated to find the best medium for chitinase enzyme production using colloidal chitin as the reference substrate. It was observed that the highest chitinase activities (0.70 U/mL) were obtained using Kawachi Medium at day 4 of fermentation. Kawachi Medium was selected as the basal medium for induction studies. Several types of inducers that included chitin colloidal and direct chitin, N-acetylglucosamine, glucosamine hydrochloride and chitosan oligosaccharides were used to investigate the feasibility of different inducers for enhancing chitinase enzyme production. The results indicated that all the tested inducers supported chitinase production by Trichoderma sp. It was suggested that the level of chitinase production were regulated or induced by the type of media and inducers used. In addition, it showed that colloidal chitin was the second best inducer after NAG. For economic considerations, colloidal chitin was chosen as the inducer for further study. The effect of different concentration of the inducer selected was studied on chitinase enzyme production. Low colloidal chitin concentration at 0.3% (w/v) gave the highest chitinase activity of 0.72 U/mL. Additionally, raw shrimp waste was also employed to induce chitinase enzyme production. Raw shrimp waste that was subjected to different pre-treatments including sun-dried, acid treated, alkali treated and enzyme treated were used to find cheaper alternative substrates for chitinase enzyme production. Sun dried and ground raw shrimp waste gave the highest chitinase enzyme production. The pretreated raw shrimp waste were also analysed for their composition include protein, moisture and ash content using proximate analysis.